Sentiment Analysis on Cash Waqf - Sri Rahayu (SMART Insight, 2022)
The purpose of this study is to analyze the sentiment resulting from the opinion of researchers through published articles related to cash waqf. The data analyzed consisted of 107 research articles indexed by Scopus in 2022. The method used is a qualitative approach with descriptive statistics from literature studies on the theme of cash waqf. The results showed that neutral sentiment was the highest with a percentage of 44.9%, followed by positive sentiment of 31.8%, negative sentiment of 23.4%. The diversity of sentiment results is obtained because of the pros and cons of cash waqf.